Support received by women with breast cancer in the event of side effects of chemotherapy - Anna Irzmańska-Hudziak; Sylwia Chabros; Dorota Weber; Andrzej Stanisławek; Joanna Wolska; Marcin Rząca; Agata Krzos; Marta Łuczyk; Elżbieta Stasiak; Katrzyna Muzyczka; Zdzisława Szadowska-Szlachetka (Kazimierz Wielki University, 2019)
Admission. Correct chemotherapy introduces many side effects. These effects, spread over time and in connection with a chronic disease such as breast cancer, put the patient in a crisis situation, which verifies the needs in terms of social support. Goal: Showing the type of social support expected and received by women treated with cytostatics for breast cancer. Material and methods: The study was conducted on a group of 110 women - patients of oncology departments of two Lublin hospitals diagnosed with breast cancer and during chemotherapy. The research tool was the author's questionnaire. The results from the obtained data were subjected to statistical analysis. Results: Patients expect information support about their illness and treatment from a doctor. In some respects, most of them receive such support. The respondents receive emotional support from their families, more than half of them received an offer of material support. There is a statistically significant relationship between education and the need for material assistance, and a relationship between the next cycle of chemotherapy and the demand for spiritual support. Conclusions: Patients treated with cytostatics, regardless of their level of education, expect information support from professionals. Such support cannot be provided by family or friends. They receive emotional support from loved ones, but during chemotherapy, the demand for spiritual and material support increases, regardless of education.